Primate body mass and dietary correlates of tooth root surface area. Issue 1 (25th October 2021) - Deutsch, Ashley R.; Dickinson, Edwin; Whichard, Victoria A.; Lagomarsino, Giulia R.; Perry, Jonathan M. G.; Kupczik, Kornelius; Hartstone‐Rose, Adam
Abstract: Objectives: This study aims to examine primate postcanine tooth root surface area (TRSA) in the context of two ecological variables (diet and bite force). We also assess scaling relationships within distinct taxonomic groups and across the order as a whole. Materials and Methods: Mandibular postcanine TRSA was measured using a three‐dimensional computed tomography (CT) method for catarrhine ( N = 27), platyrrhine ( N = 21), and strepsirrhine ( N = 24) taxa; this represents the first sample of strepsirrhines. Two different body size proxies were used: cranial geometric mean (GM) using nine linear measurements, and literature‐derived body mass (BM). Results: TRSA correlated strongly with body size, scaling with positive allometry or isometry across the order as a whole; however, scaling differed significantly between taxa for some teeth. Among Strepsirrhini, molar TRSA relative to GM differed significantly between folivores and pliant‐object feeders. Additionally, P4 TRSA relative to BM differentiated folivores from both hard‐ and pliant‐object feeders. Among Cercopithecoidea, P4 TRSA adjusted by GM differed between hard‐ and pliant‐object feeders. Discussion: Dietary signals in TRSA appear primarily driven by high frequency loading experienced by folivores. Stronger and more frequent dietary signals were observed within Strepsirrhini relative to Haplorhini. This may reflect the constraints of orthognathism within the latter, constraining the adaptability of their postcanine teeth. Finally, because of the strong correlation between TRSA and BM for each tooth locus (mean r 2 = 0.82), TRSA can be used to predict BM in fossil primates using provided equations.